Analisis Sistem Penyusunan Laporan Keuangan Konsolidasi di Yayasan Hasyim Asy’ari - Humaidi Humaidi; Susanti Susanti (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
The purpose of this study is to analyze the arrangement of financial report system in the institution unit and the report as a whole (consolidation) made by the foundation, and to reconstruct the consolidation financial report based on the (PSAK) Number 4. This study is qualitative research. The primary and secondary data are taken from the interview, observation and documentation. To analyze the data this study used Miles data stages and Huberman, there are collecting the data, data reduction, presenting and concluding the data. The result of this study shows that the financial report used by the institution in each unit is still using single entry. The financial report used by Hasyim Asy’ari Foundation does not appropriate with PSAK 4 about the consolidation report.